Hot spots and frontiers in bone-tendon interface research: a bibliometric analysis and visualization from 2000 to 2023 - Xiao, Hao; Wen, Boyuan; Yan, Dong; Li, Quansi; Yang, Yujie; Yin, Xianye; Chen, Deyu; Liu, Jiachen (Frontiers in Surgery, 2024)
Objective In this research, we investigated the current status, hotspots, frontiers, and trends of research in the field of bone-tendon interface (BTI) from 2000 to 2023, based on bibliometrics and visualization and analysis in CiteSpace, VOSviewer, and a bibliometric package in R software. Methods We collected and organized the papers in the Web of Science core collection (WoSCC) for the past 23 years (2000–2023), and extracted and analyzed the papers related to BTI. The extracted papers were bibliometrically analyzed using CiteSpace for overall publication trends, authors, countries/regions, journals, keywords, research hotspots, and frontiers. Results A total of 1,995 papers met the inclusion criteria. The number of papers published and the number of citations in the field of BTI have continued to grow steadily over the past 23 years. In terms of research contribution, the United States leads in terms of the number and quality of publications, number of citations, and collaborations with other countries, while the United Kingdom and the Netherlands lead in terms of the average number of citations. The University of Leeds publishes the largest number of papers, and among the institutions hosting the 100 most cited papers Hospital for Special Surgery takes the top spot. MCGONAGLE D has published the highest number of papers (73) in the last 10 years. The top three clusters include #0 “psoriatic arthritis”, #1 “rotator cuff repair”, and #2 “tissue engineering”. The structure and function of the BTI and its key mechanisms in the healing process are the key to research, while new therapies such as mechanical stimulation, platelet-rich plasma, mesenchymal stem cells, and biological scaffolds are hot topics and trends in research. Conclusion Over the past 23 years, global research on the BTI has expanded in both breadth and depth. The focus of research has shifted from studies concentrating on the structure of the BTI and the disease itself to new therapies such as biomaterial-based alternative treatments, mechanical stimulation, platelet-rich plasma, etc.